Microstructure and defects of 0.1P2O5–0.65ZnO–0.25(xTeO2–(1-x)MoO3) quaternary glass nanocomposites using positron annihilation and correlated experimental methods. (April 2022) - Biswas, Dipankar; Chakrabarti, Chiranjib; Das, Anindya Sundar; Ahmed, Maudud; Mukherjee, Shubharaj; Nambissan, P.M.G.
Abstract: This study reports the spectroscopic examination of positron annihilation to characterize structural defects in glass nanocomposite systems of 0.1P2 O5 –0.65ZnO–0.25( x TeO2 –(1- x )MoO3 ), consisting of two ternary ( x = 0.0 and 1.0) and several intermediate quaternary ( x = 0.05, 0.1, 0.2, 0.3, 0.4, 0.6, and 0.8) samples prepared by the melt quenching process. The lifetimes of the positrons, the relative intensities, and the parameters of the Doppler-broadened lineshape of the positron annihilation gamma ray spectra indicated porous-type defects inside the amorphous glassy matrices formed in samples of x = 0.05–0.2 and free volume defects in interfaces of the newer nanocrystallites at higher stages of modification ( x ≥ 0.3). The results of X-ray diffraction confirmed the amorphous character of the samples and transmission electron micrographs confirmed the formation of the nanocrystallites. Selected area electron diffraction patterns revealed that the nanocrystallites were superimposed on the amorphous glass matrices. The spectra of energy-dispersive X-ray analysis revealed the presence of elemental constituents of the nanocomposites according to the required stoichiometries. A detailed Rietveld analysis of the X-ray diffraction patterns was used to identify the dispersed nanocrystallites and ascertain their stoichiometries. The work here is important in the context of developing technologically relevant glass nanocomposites from metal oxides with suitable physical characteristics. However, defects like vacancies that are formed during preparation may play a crucial role in determining their physical properties as well as the formation of free volumes and new nanocrystallites, where the latter were adequately dispersed over the glassy network. This can help transform the material into novel archetypes. Graphical abstract: Image 1 Highlights: Glassy amorphousness and nanocrystallinity were observed in 0.1P2 O5 –0.65ZnO–0.25 ( x TeO2 –(1- x )MoO3 ). A full Rietveld analysis of the X-ray diffraction patterns revealed dispersed nanocrystallites. HRTEM and SAED images confirmed the presence of crystallites superimposed over the amorphous glassy network. The lifetimes of the positrons showed that defects in the composites were vacancy type or their clusters. The rates of positron trapping confirmed that vacancy-type defects were dominant over free-volume holes.